Escrevendo no caminho: ao encontro do penitente - Tavares, Regis Torquato de Araújo (2020)
I write about the poetic path that doesn’t star here and doesn’t end here. It is the middle of a path between me and Francisco Leal, between Fortaleza and Angico de Cima, countryside of Aurora, Cariri, Ceará. The process of creation is immersed in the dissertation and carries encounters with it. The process is inthe text, in the ideas and understandings that came along the way. The many possible meetings converge on Francisco Leal de Oliveira, a penitent dedicated to writing his own life in school notebooks. From Aurora, the municipality where he resides, I take back and gradually build my own notebook from childhood memories, reminiscences of trips, visits to family members, contacts with penitents. Aurora is my place of tension between what is, at the same time, familiar and passage. From this encounter with the place and with the penitent, a dialogical writing emerges presented in multiple textual genres: chronicle, short story, poem, travel story, diary, recipe, letter, biographical profile. Dissertation developed with the Laboratório de Investigação em Comunicação, Corpo e Arte – LICCA